IMPACT OF FINANCIAL DISTRESS SHOCK AGAINST FINANCIAL PERFORMANCE IN BANK MUAMALAT INDONESIA: TWO-STAGE LEAST SQUARE METHOD - M. Fauzan; Dede Ruslan; Muhammad Fitri Rahmadana (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Bank Muamalat Indonesia is able to maintain the overall stability of its financial system; however, the bank's distress level ranges from 0.10 to 0.65, and a score below 1.81 indicates a high risk of bankruptcy. The purpose of this research is to determine the simultaneous relationship between the financial performance and financial distress level of Bank Muamalat Indonesia. This research uses secondary data from 2010 to 2023, utilizing quarterly data. The analysis employs a quantitative method with simultaneous equation techniques using the Two Stage Least Square (TSLS) method. Based on the simultaneous test results, there is a simultaneous relationship between the financial performance model and financial distress, which is identified as over-identified. In the Financial Performance (ROA) equation model, financial distress has a significant negative effect, whereas CAR and NPF are not significant. However, FDR has a significant positive effect. In the Financial Distress (Z-Score) model, NPF and FDR have a significant impact, while Financial Performance (ROA) and economic growth have a significant negative impact. The implication is the importance of financial risk management and the financial health of banks. Recommendations include enhanced supervision and financial risk management, as well as policies that support stable economic growth.